Environmental Impact Assessment (EIA) and Prediction Method: Case Study - U P, Silsilah; A, Gandhimathi (Journal of Technical Education Science, 2023)
Environmental Impact Assessments (EIAs) identify or predict any potential problems in the Environment at the planning stage of proposed development projects, and concerns are addressed as the Project progresses. It is in progress. The recommendations made by the EIA may lead to the redesign of specific project components, require additional studies, and suggest mitigation measures that will alter the socio-economic viability of the Project or cause delays in project implementation [1]. The EIA's main objective is to identify significant impacts early in the project cycle so that recommendations can be incorporated into the design and cost-benefit analysis without causing substantial delays. Increase or increase design costs [1]. The EIA will lead the appropriate environmental monitoring and management planning mechanism when implementation commences. In the case of this study, the EIA method is applied to evaluate different ecological components such as physical and chemical parameters and biological and socioeconomic parameters of the project “Construction of the office complex".